Diversity and identity of Fusarium species occurring on fruits, vegetables and food grains - AVINASH P. INGLE (Smujo International, 2017)
Ingle AP. 2017. Diversity and identity of Fusarium species occurring on fruits, vegetables and food grains. Nusantara Bioscience 9: 44-51. The members of the genus Fusarium are the most important pathogens associated with different plants including crop plants, fruits, vegetables, etc. Fusarium species are mainly responsible for wilts, blights, root-rots and cankers in these plants. Fusarium spp. produces many types of mycotoxins, which can unfavorably affect human and animal health. In the present study, 48 isolates of Fusarium were recovered from various fruits, vegetables and food grains. Out of these, 23 isolates were recovered from vegetables, 14 from food grains and 11 from fruits. Further, different isolates recovered from infected plant materials were identified on the basis of morphological, cultural and microscopic characteristics. All the isolates were categorized into 11 groups. viz., F. semitectum have maximum number of isolates (10), followed by F. solani (7), F. oxysporum (5), F. equiseti (5), F. acuminatum (4), F. proliferatum (4), F. scirpi (4), F. moniliforme (3), F. tricinctum (3), F. graminearum (2) and F. culmorum (1). For the rapid identification and confirmation of identity, ITS (internal transcribed spacer) r-DNA sequencing and their comparison with sequences available in GenBank was performed using online BLAST program. ITS-rDNA sequence comparison can be used as potential and unique molecular marker for the rapid and accurate identification of different Fusarium species. Moreover, the rapid identification can help in the management of Fusarium infections in plants.